Changes in host densities and co-feeding pattern efficiently predict tick-borne encephalitis hazard in an endemic focus in northern Italy. Issue 10 (September 2019) - Rosà, Roberto; Tagliapietra, Valentina; Manica, Mattia; Arnoldi, Daniele; Hauffe, Heidi Christine; Rossi, Chiara; Rosso, Fausta; Henttonen, Heikki; Rizzoli, Annapaola
Graphical abstract: Highlights: Autumnal cooling of the prior year positively affected co-feeding ticks on mice. Co-feeding ticks on mice were positively associated with roe deer abundance. Mouse density showed a humped relationship with the number of co-feeding ticks on mice. The heaviest adult males of Apodemus flavicollis carried more co-feeding ticks. Co-feeding ticks on mice increased tick-borne encephalitis virus prevalence in mice the following year. Abstract: Tick-borne encephalitis is an important zoonosis in many parts of north-western, central and eastern Europe, Russia and the Far East, with considerable altitudinal and latitudinal shifts described during recent decades. The reported routes of transmission for TBE virus include the saliva-activated non-viraemic transmission between co-feeding ticks taking place on rodent hosts. During the period 2001–2014, a population of the yellow-necked mouse ( Apodemus flavicollis ), which is considered among the most efficient TBE competent host, especially in central and western Europe, was intensively live-trapped in a known TBE focus in the Province of Trento, Italy. Individual live-trapped mice were checked for the number and position of feeding ticks and serologically screened for TBEv antibodies. A combined effect of climatic conditions and density of both roe deer and mice on the number of co-feeding tick groups was observed. Specifically, the occurrence of co-feeding ticks on mice during the questing season was affected by autumnal cooling in the previous season. On the other hand, co-feeding occurrence was also positively associated with roe deer abundance, while mouse density showed a hump-shaped pattern. Individual features of A. flavicollis such as weight and sex also affected co-feeding occurrence with the heaviest (breeding adult) males carrying more co-feeding ticks. We also found that the overall number of co-feeding ticks on mice positively affected TBEv antibody detection in this species the following year. In conclusion, a specific combination of climatic conditions in conjunction with certain rodent and roe deer densities are the principal determinants of the number of co-feeding ticks on A. flavicollis and, consequently, TBEv circulation. These variables can be used to provide an early warning signal for a TBE hazard, thus representing a useful tool for Public Health authorities to prepare action for prevention and control within TBEv circulation areas.